INTRAUTERINE EXTRA AMNIOTIC MISOPROSTOL VERSUS VAGINAL MISOPROSTOL FOR TERMINATION OF SECOND TRIMESTER MISCARRIAGE. - Dr. Marwa Dhafir Abd-Al-Hamid; Dr. Sumaya Tahir Saihood; Dr. Marwan Kamil Aboud (Scholar Express Journals, 2022)
The study aims to compare the efficacy and safety of two different routes of administration of misoprostol; the intrauterine extra-amniotic route and vaginal route of misoprostol in a dose of 200 microgram of misoprostol every 4 hours for the termination of pregnancy in cases of second-trimester miscarriage
Keywords: Misoprostol; Miscarriage; Amniotic; Vaginal